2017
DOI: 10.3389/fneur.2017.00435
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Different Stages of Parkinson’s Disease Using Composite Index of Speed and Pen-Pressure of Sketching a Spiral

Abstract: The speed and pen-pressure while sketching a spiral are lower among Parkinson’s disease (PD) patients with higher severity of the disease. However, the correlation between these features and the severity level (SL) of PD has been reported to be 0.4. There is a need for identifying parameters with a stronger correlation for considering this for accurate diagnosis of the disease. This study has proposed the use of the Composite Index of Speed and Pen-pressure (CISP) of sketching as a feature for analyzing the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(42 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…In other words, the Parkinsonian group is typically considered as a single cluster in which all subjects share the same degree of disease severity. In Reference [92], Zham et al addressed this issue by investigating the correlation between the speed and pen pressure while sketching a spiral and the severity of disease symptoms. The strongest correlation was found with a combination of these two parameters, which turned out to be useful for the automatic differentiation between the low and high degree of severity.…”
Section: Disease Diagnosismentioning
confidence: 99%
“…In other words, the Parkinsonian group is typically considered as a single cluster in which all subjects share the same degree of disease severity. In Reference [92], Zham et al addressed this issue by investigating the correlation between the speed and pen pressure while sketching a spiral and the severity of disease symptoms. The strongest correlation was found with a combination of these two parameters, which turned out to be useful for the automatic differentiation between the low and high degree of severity.…”
Section: Disease Diagnosismentioning
confidence: 99%
“…monitoring services, PD has been a focus of early large-scale data gathering studies, such as mPower (16). Many of these approaches, like the one presented in this report, are task-based and require a patient to generate data electively (17)(18)(19)(20)(21)(22). Other approaches use background-running software to collect data from a patient's quotidian interactions with their devices (23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…The distances between the two points from the SST and DST plots of the subjects were compared and compared, and a tablet-based remote monitoring system was designed to measure the cortical and motor performances of the subjects [10]. In the studies performed, the success of the spiral analysis test in detecting early PD was demonstrated statistically [11,12].…”
Section: Introductionmentioning
confidence: 99%